ChemInform Abstract: Enolizable Carbonyls and N, O‐Acetals: A Rational Approach for Room‐Temperature Lewis Superacid‐Catalyzed Direct α‐Amidoalkylation of Ketones and Aldehydes. Issue 37 (August 2016) - Touati, Bahria; El Bouakher, Abderrahman; Taillier, Catherine; Othman, Raja Ben; Trabelsi‐Ayadi, Malika; Antoniotti, Sylvain; Dunach, Elisabet; Dalla, Vincent
Abstract: An efficient catalytic room‐temperature direct α‐amidoalkylation of ketones and aldehydes with unbiased N, O‐acetals is described.